Memory Enhancement Activity of Clitoria Ternatea (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Clitoria ternatea (Family: Fabaceae) is one of the traditional medicinal plants used as “Shanka Pushpi” an Ayurvedic medicine used to boost or enhance neurological health. The plant contains alkaloid, flavonoid, taraxerol, taraxerone, triterpenoid and anthocyanin as active chemicals that bring about its biological effects. Its extracts possess a wide range of pharmacological activities including antibacterial, anti-diabetic, anti-diarrheal, anti-fungal, anti-helmintic, antiinflammatory, antimicrobial, antioxidant, and antipyretic activities, hypolipidemia, immunomodulatory, and wound healing. This review is an attempt to compile information on various ethnomedicinal uses of memory boosting herb, butterfly pea, Clitoria ternatea. Conclusion: It has a wide spectrum of neuropharmacological benefits such as nootropic, anti-depressant, anti-stress, anxiolytic, and anticonvulsant activities
Keywords: Butterfly pea; Clitoria ternatea; Herb; Memory; Neuropharmacology; Plant